The Role of Guidance and Counseling in Improving Learning Outcomes and Self-Confidence of Grade 6 Students at MI Hadrul Ulum Cisalak - Cepi Ananda; Fina Lapyah; Tanti Ratu R.; Nurfitriani (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to explore the role of guidance counseling (BK) in improving the academic performance and self-confidence of students at MI Hadrul Ulum Cisalak. Self-confidence is considered a key factor influencing students' motivation and academic performance. This research uses a mixed-methods design, with a quantitative approach to measure the relationship between self-confidence and academic performance through questionnaires, and a qualitative approach to deepen understanding through observations. The study population consists of 30 students at MI Hadrul Ulum Cisalak, with a total sample used due to the limited population size. The results show a significant positive relationship between self-confidence and academic performance (correlation coefficient = 0.65). Students with high self-confidence tend to be more active in the learning process and have better average grades. Observational findings also reveal that the school environment and the role of the BK teacher have an important influence in building students' self-confidence. The BK program at MI Hadrul Ulum Cisalak has made a positive contribution, but still needs improvement in terms of frequency and variety of activities. Based on these findings, the study recommends increasing the frequency of the BK program, using a holistic approach, and collaborating with parents to create a more supportive learning environment. This study provides important contributions to the development of more effective BK programs in supporting the academic and psychological development of students at the elementary school level.